The immunology of diabetic cardiomyopathy - Song, Ming; Dai, Honggang; Zhou, Quan; Meng, Xiao (Frontiers in Endocrinology, 2025)
Diabetic cardiomyopathy is a notable microvascular complication of diabetes, characterized primarily by myocardial fibrosis and functional abnormalities. Long-term hyperglycemia induces excessive activation and recruitment of immune cells and triggers the cascade of inflammatory responses, resulting in systemic and local cardiac inflammation. Emerging evidence highlights the significant roles of immunology in modulating the pathology of diabetic cardiomyopathy. As the primary effectors of inflammatory reactions, immune cells are consistently present in cardiac tissue and can be recruited under pathological hyperglycemia circumstances. A disproportionate favor to proinflammatory types of immune cells and the increased proinflammatory cytokine levels mediate fibroblast proliferation, phenotypic transformation, and collagen synthesis and ultimately rise to cardiac fibrosis and hypertrophy. Meanwhile, the severity of cardiac fibrosis is also strongly associated with the diverse phenotypes and phenotypic alterations of the immune cells, including macrophages, dendritic cells, mast cells, neutrophils, and natural killer cells in innate immunity and CD4+ T lymphocytes, CD8+ T lymphocytes, and B lymphocytes in adaptive immunity. In this review, we synthesized the current analysis of the critical role played by the immune system and its components in the progression of diabetic cardiomyopathy. Finally, we highlight preclinical and clinical immune targeting strategies and translational implications.